2019
DOI: 10.1074/jbc.ra119.010339
|View full text |Cite
|
Sign up to set email alerts
|

Calibration between trigger and color: Neutralization of a genetically encoded coulombic switch and dynamic arrest precisely tune reflectin assembly

Abstract: Edited by Joseph M. Jez Reflectin proteins are widely distributed in reflective structures in cephalopods. However, only in loliginid squids are they and the subwavelength photonic structures they control dynamically tunable, driving changes in skin color for camouflage and communication. The reflectins are block copolymers with repeated canonical domains interspersed with cationic linkers. Neurotransmitter-activated signal transduction culminates in catalytic phosphorylation of the tunable reflectins' cationi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(97 citation statements)
references
References 56 publications
14
83
0
Order By: Relevance
“…Within this context, unique structural proteins known as reflectins have recently attracted substantial attention because of their key roles in the fascinating color-changing capabilities of cephalopods, such as the squid shown in Fig. 1 A , and have furthermore demonstrated their utility for unconventional biophotonic and bioelectronic technologies ( 11 40 ). For example, in vivo, Bragg stack-like ultrastructures from reflectin-based high refractive index lamellae (membrane-enclosed platelets) are responsible for the angle-dependent narrowband reflectance (iridescence) of squid iridophores, as shown in Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Within this context, unique structural proteins known as reflectins have recently attracted substantial attention because of their key roles in the fascinating color-changing capabilities of cephalopods, such as the squid shown in Fig. 1 A , and have furthermore demonstrated their utility for unconventional biophotonic and bioelectronic technologies ( 11 40 ). For example, in vivo, Bragg stack-like ultrastructures from reflectin-based high refractive index lamellae (membrane-enclosed platelets) are responsible for the angle-dependent narrowband reflectance (iridescence) of squid iridophores, as shown in Fig.…”
mentioning
confidence: 99%
“…Given reflectins’ demonstrated significance from both fundamental biology and applications perspectives, some research effort has been devoted to resolving their three-dimensional (3D) structures ( 30 , 31 , 35 39 ). For example, fibers drawn from full-length Euprymna scolopes reflectin 1a and films processed from truncated E. scolopes reflectin 1a were shown to possess secondary structural elements (i.e., α-helices or β-sheets) ( 30 , 31 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ILs, then, could potentially use ionic interactions to tune the refractive properties of reflectin for specific applications. By neutralizing the linker segments in reflectin, these linker segments are able to overcome Coulombic repulsion and re-assemble into multimeric spheres of well-defined size and dispersity [93]. The wide range of anions available in ILs could result in several different self-assembly positions for reflectin for a wide variety of applications.…”
Section: Reflectinmentioning
confidence: 99%
“…[1] Since their discovery, researchers have been working towards the development of dynamic, optically active biomimetic camouflage technologies which exploit the unique properties of reflectins. [8][9][10][11][12] Facilitating this, recent efforts have been directed toward the characterization of reflectins in vitro, revealing properties such as pH-dependent particle-size formation, [13] the differential roles of motifs and linker regions, [6] the role of key amino-acid residues, [14] reflectin conductive properties, [15,16] and the effect of small molecules on higher-order assembly. [17] Advances in the design, fabrication, and characterization of reflectin-based materials have revealed properties such as thickness-dependent coloration, [9][10][11]18,19] broad near-infra-red (NIR) reflectance, [11] and induced light scattering, [20,21] It has also been demonstrated that the thickness (and therefore optical properties) of these materials can be controlled both pre-fabrication, by varying parameters such as flow-coating angle and sample concentration, [18,19] and post-fabrication, via vapor-induced swelling, [18,19] applying uniaxial strain, [10] or proton conduction.…”
Section: Introductionmentioning
confidence: 99%